Corpos (in)visíveis: narrativas e feminismos - Ribeiro, Diana Montenegro (2022)
The feminist movements are commonly identified by international literature - particularly the European-American axis - from the “feminist waves”, which are characterized according to the socio-historical process, from the turn of the 18th century to the present day - and where some authors point out that we are living the fourth wave. This perspective of analysis may represent a hegemonic and normative view of the history of Western feminism, excluding specificities from other contexts. Brazilian feminisms have characteristics that are similar to the landmarks of other feminist movements, but they also have particularities. We highlight the importance of intersectionality, where, through black feminism, issues of race and class are added to gender issues. In feminisms, the body gains prominence, whether when fighting for objectives that involve it or when making it the protest itself, a political tool. Given the Brazilian reality, with stereotypes built and explored about women's bodies throughout history, it is only possible for some bodies to live and protest in safety. In this doctoral research, which is committed to feminist epistemologies and methodologies, based on two blocks of studies, we problematize the new assemblages that emerge on or from women's bodies to answer the following starting question “how if (re) construct Brazilian feminist narratives around women's bodies today? In the first block of studies, we analyzed feminist and autobiographical narratives of Brazilian women present in three Brazilian feminist blogs. In the second block, we have as a sample the narratives of Law Projects proposed by Marielle Franco, which, directly or indirectly, centralize women's bodies. Both samples bring characteristics of intersectionality and the feminist fourth wave and are coded and analyzed from the Thematic Analysis. In block 1, the following themes are listed and problematized: 1. Standard of Beauty/Stereotypes; 2. Work/Study; 3. Blackness/Racism; 4. Violence; 5. Sexuality/Gender; 6. Health/Abortion. And in block 2: 1. Negritude/Racism; 2. Violence against women; 3. LBTQIA+ Causes; 4. Maternity/Abortion. .